Wi-Li-Fi an Innovative Wireless Network Architecture for Future IOT Applications - Selvi, S. Arunmozhi; Perumal, P. Sivananaintha; Rajesh, R.S (International Journal of Computer Sciences and Engineering, 2025)
Wi-Fi plays an important role in the current scenario. The whole world runs at the back of Wi-Fi technology for their seamless data connectivity. As the usage increases more and more the technology steps back in his performance slightly. The performance is based on the uninterrupted connectivity, the speed of data transfer and the network traffic. Researchers say Light Fidelity (Li-Fi) uses light emitting diodes (LEDs) for high-speed wireless communications. VLC (visual light Communication) is the channel for Li-Fi to transmit data nearly 200 Gigabits/sec. Since employing a different range of the electromagnetic spectrum from radio frequency (RF) communications, Li-Fi (Light Fidelity) enters in this phase of Wi-Fi to take part in the performance based upon the speed of data transfer. Hence, a combination of Li-Fi and RF networks becomes a challenging work in future indoor wireless communications. Thus the backdrops of both Li-Fi and Wi-Fi are complementing each other by their performance. Wi-Fi is used for uplink and Li-Fi can be used for downlink. With this strategy, all researchers have focused in this area by integrating the Wi-Fi and Li-Fi for seamless data transmission especially in the indoor environment. This hybrid can be called easily abbreviated as Wi-Li-Fi. There are many challenges combining the both different types of networks. A newly Hybrid Wi-Li-Fi network is proposed and its performances are compared with standalone Li-Fi and Wi-Fi networks, metrics such as Throughput, Energy consumption and data loss, when the end users are at different distance from the Access point